Investigating English Vowel Reduction in Pronunciation of EFL Teachers of Schools. (14th October 2016) - Gowhary, Habib; Azizifar, Akbar; Rezaei, Sahar
Abstract: One of the skills of speaking in a foreign language which has its own difficulties is correct pronunciation. English is not an exception to this rule and one of the challenging parts of this language is the process called vowel reduction which has always been problematic for language learners. This study has been conducted to investigate observing of English vowel reduction in pronunciation of EFL teachers of high schools in Ilam city. For this purpose, it examines the effects of gender, experience and academic degree on the observing of vowel reduction in derivative and function words. The participants of the study were 60 EFL teachers with B.A., M.A., and PhD degrees teaching English in high schools of Ilam city, 30 being male and 30 female. They ranged from 1 to 30 years of teaching experience. The instrument used in the study was a checklist comprising of 30 sentences containing derivative and function words in which the vowel reduction occurs. The results showed that there was a meaningful relationship between gender of the participants and vowel reduction in general and vowel reduction in derivative words but not with function words. Males performed better than females in pronouncing the reduced vowels. There was a meaningful relationship between teaching experience and vowel reduction in general, vowel reduction in derivative words and in function words. The group with 16 to 20 years of teaching experience had the highest mean. The second highest mean belonged to the group of 21 to 25 years of experience. The results also showed that until 20 years of teaching experience, the means of pronunciation increase and after that decrease gradually. There was a meaningful relationship between academic degree and vowel reduction in general, vowel reduction in derivative words and in function words. The PhDs had the highest mean and did better than the MAs and BAs.